HIV Status in Sero-Discordant Couples: Prevalence and Pattern among Pregnant Women in Plateau State, Nigeria - Magaji, FA; Ocheke, AN; Pam, VC; Afolaramin, T; , Musa J; Sagay, AS; Zoakah, AI (Journal of Clinical Research In HIV AIDS And Prevention, 2018)
Nigeria is one of the high-burden countries in sub-Saharan Africa for HIV/AIDS and contributes to reproductive health morbidities and mortalities. This study was aimed at determining the prevalence of HIV-discordant rate among pregnant women in Plateau state Nigeria. The study sought to determine the prevalence and trend of HIV sero-discordance among pregnant women in Plateau state, Nigeria. The study was a 5-year descriptive analysis of HIV sero-discordance among pregnant women accessing prenatal care and their partners in Plateau state, Nigeria based on data generated between January 2012 and December 2016. The data was disaggregated by year, HIV concordant negative, HIV concordant positive, and HIV sero-discordant prevalence in the software and analysis were done using excel to obtained the proportions and trend of HIV sero-discordant prevalence among the antenatal population. Out of a total of 7,851 partners of pregnant women studied, 969 (16.3%) were HIV sero-discordant, 5,795 (73.8%) were HIV concordant negative, and 773 (9.9%) were HIV concordant positive. HIV sero-discordant positive males accounted for 12.3% while females were 4.0%. The prevalence of HIV sero-discordance was low with a high proportion of HIV positive male partners in Plateau state with grave public health implications for new HIV infections among partners and eroding the gains made in the Prevention of mother-to-child transmission of HIV.
Keywords: HIV; Sero-discordance; Pregnancy; Partner; Plateau State.